Characteristics of bolus formation and propagation from breaking internal waves on shelf slopes. (19th February 2016) - Moore, Christine D.; Koseff, Jeffrey R.; Hult, Erin L.
Abstract : A series of laboratory experiments was conducted to study the formation of internal boluses through the run up of periodic internal wave trains on a uniform slope/shelf topography in a two-layer stratified fluid system. In the experiments, the forcing parameters of the incident waves (wave amplitude and frequency) are varied for constant slope angle and layer depths. Simultaneous particle image velocimetry (PIV) and planar laser-induced fluorescence (PLIF) measurements are used to calculate high resolution, two-dimensional velocity and density fields. Over the range of wave forcing conditions, four bolus formation types were observed: backward overturning into a coherent bolus, top breaking into a turbulent bolus, top breaking into a turbulent surge and forward breaking into a turbulent surge. Wave forcing parameters, including a wave Froude number Fr, a wave Reynolds number Re and a wave steepness parameter ka_0, are used to relate initial wave forcing to a dominant bolus formation mechanism. Bolus characteristics, including the bolus propagation speed and turbulent components, are also related to wave forcing. Results indicate that for Fr>0.20 and ka_0>0.40, the generated boluses become more turbulent in nature. As wave forcing continues to increase further, boluses are no longer able to form.